2012
DOI: 10.1161/circimaging.111.968859
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Response in Hypertrophic Cardiomyopathy

Abstract: Background-Abnormal left ventricular (LV) deformational mechanics have been demonstrated in patients withhypertrophic cardiomyopathy (HCM) at rest, but there is a lack of information on their adaptation to exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 38 publications
1
33
1
2
Order By: Relevance
“…Contraction of the LV is achieved by myocyte shortening of the oblique and circumferential fibres and, following a complex rearrangement of the microstructure of the LV (LeGrice et al 1995), results in a twisting motion around the LV long axis and circumferential shortening, respectively (Sengupta et al 2008). Previous studies have shown that LV twist plays an essential role in the efficient ejection of blood (Soullier et al 2012). Additionally, LV twist appears to be related to the regional O 2 distribution across the LV muscle (Beyar & Sideman, 1986) and has been implicated in stress sensing (Vendelin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Contraction of the LV is achieved by myocyte shortening of the oblique and circumferential fibres and, following a complex rearrangement of the microstructure of the LV (LeGrice et al 1995), results in a twisting motion around the LV long axis and circumferential shortening, respectively (Sengupta et al 2008). Previous studies have shown that LV twist plays an essential role in the efficient ejection of blood (Soullier et al 2012). Additionally, LV twist appears to be related to the regional O 2 distribution across the LV muscle (Beyar & Sideman, 1986) and has been implicated in stress sensing (Vendelin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…скручивание ЛЖ не отличалось от контроля во время нагрузочной пробы и было до-стоверно выше по сравнению с систолической СН [39]. В работе других авторов у лиц с диастолической СН и со-храненной ФВ ЛЖ получены меньшие показатели при-роста скручивания и раскручивания по сравнению с конт-ролем при физической нагрузке [17,40]. Представленные факты роли скручивания и раскручивания при диасто-лической дисфункции подчас сложно объяснить, поэтому необходимы дальнейшие исследования для разреше-ния этих противоречий [12].…”
Section: клиническое значение скручивания и рас-кручиванияunclassified
“…Несмотря на сохраненную амплитуду скручивания и не-значительное снижение скорости диастолического рас-кручивания, у пациентов с гипертрофической кардио-миопатией наблюдается существенно более низкий при-Ротация, скручивание и раскручивание левого желудочка рост скручивания, скорости скручивания и раскручи-вания во время физической нагрузки по сравнению с контролем. Более того, прирост скручивания может во-обще отсутствовать, указывая на полное истощение ком-пенсаторных резервов, что может объяснять появление ДСН в этой группе [17,40]. Динамическая обструкция выносящего тракта ЛЖ у лиц с гипертрофической кар-диомиопатией также сопровождается задержкой рас-кручивания.…”
Section: клиническое значение скручивания и рас-кручиванияunclassified
“…They had reduced and delayed UTR with reduced systolic-diastolic coupling efficiency by twist-untwist mechanics. 20 …”
Section: Comprehensive Use Of Cardiopulmonary Exercise Testing Identimentioning
confidence: 99%